Bile cast nephropathy; a neglected entity - Rodrigo Alvarez; Ramin Tolouian (Society of Diabetic Nephropathy Prevention, 2023)
This study investigates the role of bile cast nephropathy (BCN) in acute kidney injury associated with cholestatic liver disease. Bile cast nephropathy is characterized by kidney injury due to, bile-related factors, distinct from hepatorenal syndrome (HRS) linked to hemodynamic changes in liver disease. The mechanisms of BCN include oxidative damage, tubular toxicity, and obstructive physiology. Diagnosis is typically through biopsy, although alternatives like trans-jugular biopsy are considered due to bleeding risks. Treatment targets underlying causes of hyperbilirubinemia, and extracorporeal therapies like plasmapheresis and molecular adsorbent recycling system show potential efficacy. Awareness and further research on noninvasive diagnostic methods for BCN are recommended.